Association between serum 25-hydroxy vitamin D level and menstrual cycle length and regularity: A cross-sectional observational study - Vinita Singh; Neelam Tamar; Zamir Lone; Esha Das; Rajshree Sahu; Sagarika Majumdar (Shahid Sadoughi University of Medical Sciences, 2021)
Abstract Background: Research examining the role of vitamin D deficiency and the development of menstrual disorders in women is of widespread interest. Studies have been published showing that supplementation with high-dose vitamin D can lead to the restoration of the menstrual cycle. We lack adequate information regarding the effect of vitamin D levels on the physiology of menstruation and further on fertility in women of reproductive age due to the contradictory results reported by studies. Objective: To study the association of 25-hydroxy vitamin D with menstrual cycle characteristics including long and short cycle length and cycle irregularity. Materials and Methods: In this cross-sectional study, serum vitamin D levels of 166 women attending an outpatient department with menstrual irregularities after excluding all obvious causes of menstrual disorders (n = 83) between April-June 2019 were measured and were compared with women of similar profiles with complaints other than menstrual irregularities (n = 83). Results: A decreased level of vitamin D was associated with a 13.3 times odds of an irregular cycle (OR (95% CI): 13.30 (5.79-30.60), p < 0.001). 25-hydroxy vitamin D was not associated with age or body mass index. We found a significant difference (p < 0.001) in mean vitamin D levels among the females with irregular cycles vs. regular cycles. Conclusion: Vitamin D plays a role in the physiology of reproduction specific to the menstrual cycle and ovulation. Long-term prospective studies assessing the exact cutoff value and the exact dose of supplementation required are needed.